Taylor House - Frank Harmon (Oz, 2003)
“Like a sea hawk’s nest overlooking the sea” —that was the way industrial designer Jim Taylor described the vacation house he and his wife, Janice, wanted to build on Scotland Cay, one of the exotic Abacos Islands in the Bahamas.